2011
DOI: 10.1152/jn.00781.2010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motor cortex neuronal networks by rTMS: comparison of local and remote effects of six different protocols of stimulation

Abstract: Repetitive transcranial magnetic stimulation (rTMS) of human motor cortex can produce long-lasting changes in the excitability of excitatory and inhibitory neuronal networks. The effects of rTMS depend critically on stimulus frequency. The aim of our present study was to compare the effects of different rTMS protocols. We compared the aftereffects of 6 different rTMS protocols [paired associative stimulation at interstimulus intervals of 25 (PAS(25)) and 10 ms (PAS(10)); theta burst stimulation delivered as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
183
5
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(214 citation statements)
references
References 37 publications
14
183
5
6
Order By: Relevance
“…In light of this result, it is not clear why MEP amplitude was significantly decreased following cTBS but not significantly facilitated following iTBS in the current study. One possible explanation is smaller variability following cTBS than iTBS; previous studies have shown smaller SEM following cTBS than iTBS [2,13] and in the current study, the coefficient of variation was smaller for cTBS than iTBS (Fig. 1).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In light of this result, it is not clear why MEP amplitude was significantly decreased following cTBS but not significantly facilitated following iTBS in the current study. One possible explanation is smaller variability following cTBS than iTBS; previous studies have shown smaller SEM following cTBS than iTBS [2,13] and in the current study, the coefficient of variation was smaller for cTBS than iTBS (Fig. 1).…”
Section: Discussioncontrasting
confidence: 41%
“…Indeed, a recent study demonstrated large variability when comparing the effects of six NBS protocols [2]. The effect of intersubject variability on responses to NBS protocols at the group level has been discussed above.…”
Section: Discussionmentioning
confidence: 97%
“…A number of factors have been identified that influence the direction and magnitude of induced effects, including the age of study participants, their genetics, and their history of physical activity (Ridding and Ziemann, 2010). Although initial studies suggested TBS protocols were capable of inducing robust LTP and LTD-like plasticity in the human M1 (Huang et al, 2007;Huang et al, 2005), the response to stimulation can vary considerably between individuals (Hamada et al, 2013) and between studies (Di Lazzaro et al, 2011;Gentner et al, 2008;Goldsworthy et al, 2014a, b;Goldsworthy et al, 2012a, b;Hasan et al, 2012;McAllister et al, 2011;Todd et al, 2009;Vallence et al, 2013;Zafar et al, 2008). Most studies use a standard MEP amplitude of ~1 mV to probe the plasticity response to TBS.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies report significant changes in corticospinal excitability following application of rTMS (e.g. Di Lazzaro et al 2011;Huang et al 2007;Huang et al 2005;Stefan et al 2000) a number of others do not (Clow et al 2014;Goldsworthy et al 2012a;Hamada et al 2013;McAllister et al 2013;McAllister et al 2011), highlighting that the response to rTMS is rather variable. Large inter-and intra-subject NIBS response variability is a limiting factor in both basic and applied research .…”
mentioning
confidence: 99%